Student Perceptions of Soft Skills Multisource Feedback in a Professional Athletic Training Program. - Davlin-Pater, Christina (Internet Journal of Allied Health Sciences & Practice, 2023)
Purpose: A new multi-source soft skills assessment tool and process was used in an entry-level Master of Science in athletic training education program. The goal was to provide students with individualized feedback related to soft skills that would serve to facilitate improvement and growth. The feedback process included self-reflection, goal setting, and follow-ups. This study aims to examine athletic training students' perceptions of a new, multisource soft-skills assessment process and the feedback they received. Methods: A convenience sample of 27 students enrolled in a graduate-level, CAATE-accredited athletic training education program participated in the study. At the beginning of a semester participants received an individualized multi-source soft skills feedback report based on data collected the previous semester using the Athletic Training Student - Soft Skills Assessment (ATS-SSA) instrument which includes 11 soft skill themes. Participants completed 1 survey designed to assess initial impressions of the feedback and 2 assignments focused on reflection and goal setting. One week before the end of the term, students completed a second survey to assess final impressions. Surveys included Likert scale and open response questions. Results: The process and feedback were viewed favorably. Feedback was considered fair, useful, and easy to understand. Participants recognized benefits from receiving multi-source feedback from credible evaluators. The majority of participants indicated a willingness to invest in efforts to improve. Conclusions: Preliminary findings suggest that the ATS-SSA Instrument and associated feedback process can provide worthwhile and beneficial feedback to athletic training students.